Nanomaterials in the Environment: Perspectives on in Vivo Terrestrial Toxicity Testing - Mendonça, Monique C. P.; Rizoli, Cintia; Ávila, Daiana S.; Amorim, Mónica J. B.; de Jesus, Marcelo B. (Frontiers in Environmental Science, 2017)
Over the last decade, engineered nanomaterials (NMs) brought a revolutionary development in many sectors of human life including electronics, paints, textiles, food, agriculture, and health care. However, the exponential growth in the number of NMs applications resulted in uncertainties regarding their environmental impacts. Currently, the common approach for assessing the toxicity of NMs such as, carbon—(fullerenes, single- and multi-walled carbon nanotubes), mineral—(gold and silver nanoparticles, cerium and zinc oxide, silicon and titanium dioxide), and organic-based NMs (dendrimers) includes standard guidelines applied to all chemical compounds. Nevertheless, NMs differ from traditional materials as their physicochemical and surface properties influence the toxic rather than their composition alone. Considering such NMs specificities, adaptations in some methods are necessary to ensure that environmental and human health risks are accurately investigated. In this context, the focus of this mini-review is to summarize the current knowledge in nanotoxicology regarding relevant organisms and experimental assays for assessing the terrestrial toxicity of NMs.